2013
DOI: 10.1002/tie.21531
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Green Supply Chain in Emerging Economies

Abstract: In spite of the burgeoning interest in green supply chain management in Western developed countries and large emerging economies, little research exists on the topic in small emerging and developing countries. In this study, we surveyed firms based in Dubai to identify the main drivers of green supply chain management and their impact on supply chain greening. We discuss theoretical and managerial implications of the findings. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 75 publications
1
32
1
Order By: Relevance
“…Hsu, Choon Tan, HanimMohamad Zailani, and Jayaraman (2013) studied the drivers that affect GSCM initiatives by Malaysian manufacturers, and showed that customer pressure significantly influences GSCM adoption. This conclusion is contrary to that reported by BenBrik et al (2013) in Dubai.Hence, these differences emphasize that there are several gaps in the understanding and awareness of sustainability issues in emerging economies.Recent studies demonstrated the sustainability evolution in India(Balaji & Arshinder, 2016;Gopal & Thakkar, 2016;Mani et al, 2018;…”
contrasting
confidence: 97%
See 3 more Smart Citations
“…Hsu, Choon Tan, HanimMohamad Zailani, and Jayaraman (2013) studied the drivers that affect GSCM initiatives by Malaysian manufacturers, and showed that customer pressure significantly influences GSCM adoption. This conclusion is contrary to that reported by BenBrik et al (2013) in Dubai.Hence, these differences emphasize that there are several gaps in the understanding and awareness of sustainability issues in emerging economies.Recent studies demonstrated the sustainability evolution in India(Balaji & Arshinder, 2016;Gopal & Thakkar, 2016;Mani et al, 2018;…”
contrasting
confidence: 97%
“…To analyze GSCM drivers, Ben Brik et al. () considered the Dubai context. The study's results are interesting, because the authors showed that government regulations fail in emerging economies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In UAE, the construction sector is growing at a rapid pace and resulted in environmentally unfriendly projects (Ben Brik et al, 2013). Further UAE leads the other countries in per capita CO2 emissions according to World Bank report (2009) and is estimated to be 22.6 metric tons per capita.…”
Section: Introductionmentioning
confidence: 99%